2012
DOI: 10.1002/mame.201200028
|View full text |Cite
|
Sign up to set email alerts
|

Piezomorphic Materials

Abstract: ---------The development of stress-induced morphing materials which are described as piezomorphic materials is reported. The development of a piezomorphic material is achieved by introducing spatial dependency into the compliance matrix describing the elastic response of a material capable of undergoing large strain deformation. In other words, it is necessary to produce an elastically gradient material. This is achieved through modification of the microstructure of the compliant material to display gradient t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…The energy absorption of functionally graded regular hexagonal honeycombs has been observed to be highly sensitive to the type of gradient topology used, especially under very high dynamic compressive loading and during the early stages of crushing [18]. Gradient and graded-type open cell foams produced and characterised by Alderson et al have shown overall unusual deformation mechanisms under tensile loading [19]. Gradient cellular tessellations with graded cell-wall aspect ratios and internal cell angles have been studied by Hou et al as potential fillers for sandwich beams subjected to three-point bending tests [20].…”
Section: Introductionmentioning
confidence: 99%
“…The energy absorption of functionally graded regular hexagonal honeycombs has been observed to be highly sensitive to the type of gradient topology used, especially under very high dynamic compressive loading and during the early stages of crushing [18]. Gradient and graded-type open cell foams produced and characterised by Alderson et al have shown overall unusual deformation mechanisms under tensile loading [19]. Gradient cellular tessellations with graded cell-wall aspect ratios and internal cell angles have been studied by Hou et al as potential fillers for sandwich beams subjected to three-point bending tests [20].…”
Section: Introductionmentioning
confidence: 99%
“…It provides a way to fabricate dome-like complicated structures without the necessity of using complex techniques or additional machining. Moreover, NPR materials also exhibit variable permeability [129][130][131], shape memory [112,[132][133][134], abrasive wear resistance [135], etc.…”
Section: Other Specific Propertiesmentioning
confidence: 99%
“…Therefore, to address the above limitations, the auxetic nanofiber materials have been introduced in the recent days. The auxetic material possesses adequate cell responsive and excellent mechanical properties such as flexibility, indentation resistance, fracture toughness, resilience, vibration control, shear resistance and deformation mechanism compared to conventional material of the same origin due to their unique structural designed patterns [1,[14][15][16][17][18]. The auxetic patterned materials have the ability to undergo wider when stretched, thinner when compressed and behave synclastically on bending [19][20][21].…”
Section: Introductionmentioning
confidence: 99%